2020
DOI: 10.2196/24694
|View full text |Cite
|
Sign up to set email alerts
|

Time Trends of the Public’s Attention Toward Suicide During the COVID-19 Pandemic: Retrospective, Longitudinal Time-Series Study

Abstract: Background The COVID-19 pandemic has overwhelmed health care systems around the world. Emerging evidence has suggested that substantially few patients seek help for suicidality at clinical settings during the COVID-19 pandemic, which has elicited concerns of an imminent mental health crisis as the course of the pandemic continues to unfold. Clarifying the relationship between the public’s attention to knowledge about suicide and the public’s attention to knowledge about the COVID-19 pandemic may pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…The ability to quickly track recent population behaviour might become an advantage, and in such an environment, GT is a powerful tool for tracing public interest. Other studies have used GT to monitor public concerns related to medical, social, and political issues [ 12 , 59 , 60 ]. This type of analysis is a modern alternative to smaller cross-sectional surveys with fewer data and longer time lag.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to quickly track recent population behaviour might become an advantage, and in such an environment, GT is a powerful tool for tracing public interest. Other studies have used GT to monitor public concerns related to medical, social, and political issues [ 12 , 59 , 60 ]. This type of analysis is a modern alternative to smaller cross-sectional surveys with fewer data and longer time lag.…”
Section: Discussionmentioning
confidence: 99%
“…Google Trends (GT) is gaining popularity for exploring online social behavior and predicting disease outbreaks and pandemics. This novel tool has attracted a larger scientific community, and Trends analyses have been used in various scientific fields to predict relevant medical, social, and political findings [ 11 , 12 , 13 ]. As the situation during the COVID-19 pandemic changes rapidly, a real-time data analysis would be helpful to assess the current information about public interest and concerns.…”
Section: Introductionmentioning
confidence: 99%
“…People were more sensitive to negative events during critics. A previous study found that several anticontagion policies were associated with search interest levels for the term “suicide” in the online media ( 34 ). This study found that the impact indexes of suicide events were higher during COVID-19 than before COVID-19 the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that the COVID-19 pandemic has affected the countries of the world differently according to the public health and sanitary measures adopted (Burnett et al, 2020 ). The effects of social distancing and quarantine on mental health during the COVID-19 pandemic are noticeably similar to those of traumatic events, resulting in common observable disorders such as major depression, post-traumatic stress disorder, anxiety disorders, increased alcohol and drug use, and suicide attempts (Mari & Oquendo, 2020 ).…”
Section: Introductionmentioning
confidence: 99%